2021
DOI: 10.1177/15579883211049027
|View full text |Cite
|
Sign up to set email alerts
|

Risky Business: Increasing Fertility Knowledge of Men in the General Public Using the Mobile Health Application Infotility XY

Abstract: Male infertility presents a public health concern. As most men wish to become fathers, it is important to increase men’s awareness of infertility risk factors. We developed a mobile health application (mHealth app), Infotility XY, to promote men’s reproductive health. This study evaluates whether use of the app led to increased knowledge of infertility risk factors, and whether knowledge change was associated with participants’ sociodemographic characteristics and/or app usage. Participants were recruited betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…Quantitative data indicated that participants’ knowledge of factors relating to male infertility was limited. These findings are not dissimilar to previous research using the same scale, often finding generally low levels of fertility knowledge despite high self-rated perceived knowledge ( Daumler et al, 2016 ; Kruglova et al, 2021 ). Re-scoring Daumler et al’s (2016) scale based on our knowledge and updated research evidence on factors relating to male infertility slightly improved participants’ knowledge scores, indicating that our sample’s knowledge about factors currently known to impact male infertility was better than initially indicated.…”
Section: Discussioncontrasting
confidence: 55%
“…Quantitative data indicated that participants’ knowledge of factors relating to male infertility was limited. These findings are not dissimilar to previous research using the same scale, often finding generally low levels of fertility knowledge despite high self-rated perceived knowledge ( Daumler et al, 2016 ; Kruglova et al, 2021 ). Re-scoring Daumler et al’s (2016) scale based on our knowledge and updated research evidence on factors relating to male infertility slightly improved participants’ knowledge scores, indicating that our sample’s knowledge about factors currently known to impact male infertility was better than initially indicated.…”
Section: Discussioncontrasting
confidence: 55%
“…YO Sperm Test Wi-Fi can make patients feel that they are participating in the management of their disease. The (31). Their study showed evidence of the feasibility of MHAs to improve men's knowledge about fertility, about risks factor.…”
Section: Discussionmentioning
confidence: 98%
“…However, the degree of “Infotility” use was not correlated with demographics, mental health, or diagnostic results in men (Miner et al, 2022). Moreover, Kruglova, Gelgoot, et al (2021) evaluated “Infotility XY,” a mobile application for increasing reproductive knowledge of men. They reported that “Infotility XY” increased fertility knowledge and awareness of infertility risk factors.…”
Section: Discussionmentioning
confidence: 99%